Coupling of Tree Growth and Photosynthetic Carbon Uptake Across Six North American Forests. Issue 4 (18th April 2022) - Teets, Aaron; Moore, David J. P.; Alexander, M. Ross; Blanken, Peter D.; Bohrer, Gil; Burns, Sean P.; Carbone, Mariah S.; Ducey, Mark J.; Fraver, Shawn; Gough, Christopher M.; Hollinger, David Y.; Koch, George; et al.
Abstract: Linking biometric measurements of stand‐level biomass growth to tower‐based measurements of carbon uptake—gross primary productivity and net ecosystem productivity—has been the focus of numerous ecosystem‐level studies aimed to better understand the factors regulating carbon allocation to slow‐turnover wood biomass pools. However, few of these studies have investigated the importance of previous year uptake to growth. We tested the relationship between wood biomass increment (WBI) and different temporal periods of carbon uptake from the current and previous years to investigate the potential lagged allocation of fixed carbon to growth among six mature, temperate forests. We found WBI was strongly correlated to carbon uptake across space (i.e., long‐term averages at the different sites) but on annual timescales, WBI was much less related to carbon uptake, suggesting a temporal mismatch between C fixation and allocation to biomass. We detected lags in allocation of the previous year's carbon uptake to WBI at three of the six sites. Sites with higher annual WBI had overall stronger correlations to carbon uptake, with the strongest correlations to carbon uptake from the previous year. Only one site had WBI with strong positive relationships to current year uptake and not the previous year. Forests with low rates of WBI demonstrated weak correlations to carbon uptake from the previous year and stronger relationships to current year climate conditions. Our work shows an important, but not universal, role of lagged allocation of the previous year's carbon uptake to growth in temperate forests. Plain Language Summary: We compared the interannual variability of stand‐level biomass growth (estimated from annual tree‐level measurements) to carbon uptake (measured from towers monitoring gas exchange over forest canopies) to identify temporal mismatches between the two processes. We used data from multiple forested sites with long‐term measurements of carbon uptake to ask the question: is there a consistent temporal offset between the uptake of carbon and the allocation to plant biomass? We found that the relationship between growth and carbon uptake varies among sites, and there was no consistent temporal offset between the uptake of carbon and allocation to biomass growth. Sites with higher growth rates had higher interannual variability, and more apparent coupling between biomass growth and carbon uptake from the previous year. Forests with lower growth rates had weaker relationships with carbon uptake and stronger coupling with current year environmental conditions. We demonstrate that temporal lags between carbon uptake and allocation to growth are not universal among these temperate forests, and the carry‐over of uptake stored from the previous year is not as critical in slow‐growing forests, compared to fast‐growing forests, likely due to lower demands for growth. This work helps to clarify the limitations on the growth of slow‐turnover wood biomass. Key Points: We found evidence for lags in allocation of previous year's carbon uptake to wood biomass increment (WBI) at three of six sites studied Sites with high annual WBI demonstrated strong correlations to carbon uptake, with the strongest correlations including previous year uptake WBI was less tightly coupled to carbon uptake in less productive forests that also exhibited low interannual variability in WBI